A Pareto Efficiency Rationale for the Welfare State - Stefan Napel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Can fiscal policy raise utility for all in dynamic economies with unobservable agent heterogeneity, when missing credit and insurance markets affect incentives to invest in human capital? If so, should the state provide transfers to the poor in the form of cash or in kind? In an occupational choice model, we show (a) every competitive equilib- rium is interim-Pareto dominated by a policy providing education subsidies financed by income taxes, and (b) transfers conditional on educational investments similarly dom- inate unconditional transfers. The policies also result in macroeconomic improvements (higher per capita income and upward mobility, lower wage dispersion).
Keywords: C72; C73; D82; 330